2008
DOI: 10.1007/s11606-007-0482-z
|View full text |Cite
|
Sign up to set email alerts
|

An Electronic Medical Record (EMR)-Based Intervention to Reduce Polypharmacy and Falls in an Ambulatory Rural Elderly Population

Abstract: BACKGROUND: Falls are the leading cause of injuryrelated deaths in the aging population. Electronic medical record (EMR) systems can identify at-risk patients and enable interventions to decrease risk factors for falls. OBJECTIVE:The objectives of this study were to evaluate an EMR-based intervention to reduce overall medication use, psychoactive medication use, and occurrence of falls in an ambulatory elderly population at risk for falls. DESIGN:Prospective, randomized by clinic site. PATIENTS/PARTICIPANTS:Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 25 publications
4
101
0
Order By: Relevance
“…The electronic health record (EHR) may improve health care delivery [1][2][3][4][5][6] by facilitating physician communication about medications, 3,7 enhancing documentation, 4,8,9 increasing effi ciency, [8][9][10][11][12] and fostering information sharing and responsibility with patients. 10,11 Implementation is often costly, 13 takes time and computer expertise, 14 and has unanticipated consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic health record (EHR) may improve health care delivery [1][2][3][4][5][6] by facilitating physician communication about medications, 3,7 enhancing documentation, 4,8,9 increasing effi ciency, [8][9][10][11][12] and fostering information sharing and responsibility with patients. 10,11 Implementation is often costly, 13 takes time and computer expertise, 14 and has unanticipated consequences.…”
Section: Introductionmentioning
confidence: 99%
“…51 Trials aiming to reduce overall medication among community-dwelling elderly patients have reported significant reductions in the number of total falls and fall-related injuries. [52][53][54] However, it has been concluded that patient compliance with permanent withdrawal may be difficult to achieve. 54 This is largely due to the negative effects experienced by individuals stopping medications that have previously been relied upon for relief of psychosomatic symptoms including insomnia and anxiety.…”
Section: Interventions Aimed At Preventing Subsequent Fallsmentioning
confidence: 99%
“…A greater number of prescribed drugs has been shown to substantially increase the possibility of adverse effects; however, an exact number has not been determined (11)(12) . In the scientific literature, the use of four or more drugs per day has been considered a risk factor for falls among the older adult population (13) . Some studies have examined the incidence of falls among older adults taking certain types of medications, but few authors have correlated the number of drugs with the risk of falls, and even fewer have targeted populations with a history of falls (14)(15) .…”
Section: Introductionmentioning
confidence: 99%